Penguatan Ekonomi Lokal melalui Peningkatan Kualitas Produksi dan Digitalisasi Pemasaran Ikan Asin di Kampung Siabang - Arini, Indah; Handayani, Susi (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
The salted fish industry in Kampung Siabang, Kelurahan 5 Ulu, Seberang Ulu 1 District faces challenges such as production hygiene standards, unattractive packaging, no brand identity, and minimal use of digital marketing, resulting in low product competitiveness. This community service program aims to improve production and marketing quality through training in hygienic production standardization, packaging, branding, and digital marketing. The method used is a participatory approach with training, direct practice, and evaluation. The results show an increase in the durability of salted fish products, more attractive packaging with product labels, and an increase in the number of business actors using digital media for marketing. This program is effective in increasing the competitiveness of the salted fish industry, although further assistance is still needed.